The development of a back pain scale for Tswana speaking individuals - Yazbek, Michelle (My University, 2016)
Pain is a subjective sensation and is difficult to measure. Quantifying pain provides a measure of assessing effectiveness of treatment and behaviour of the patient’s pain. In Africa unlike in the developed world, a paucity of research into the measurement of pain exists. Historically, Anglo-American scales have been used to measure pain in Africa. Aim: The aim of this thesis was to develop a back pain scale for use in Tswana speaking South Africans. Methods: Four hundred and forty participants from different education, gender and age groups participated in five studies. Study One developed new scales: Colour Analogue Scale(CAS green- red), modified Wong-Baker Faces Pain Scale (WBFPS three faces) , Ascending Injection Scale, Injection Size Scale, Ascending Coin Scale, Coin Heap Scale and previously used scales Visual Analogue Scale (VAS), CAS (white-red), WBFPS (six faces). Study Two tested these scales in 100 asymptomatic participants. “No pain” “”worst pain” was marked on original and reversed scales. Since no significant difference existed between the original and reversed versions, reversed versions were not taken further. In Study Three 40 back pain sufferers developed a Tswana Verbal Descriptive Scale. This was then tested together with the scales from the previous studies, in Study Four, in 250 Tswana individuals with back pain. Pain perception was marked on all scales. Study Five tested the Ascending Injection Scale and the Ascending Coin Scale (best scales from Study Four) and a right angle Triangle Scale in 50 back pain sufferers. “No pain”, “worst pain” and “present pain” perception was marked on all scales. Results: The Ascending Injection Scale was found to be the best understood pain scale in Tswana speaking, back pain sufferers. Conclusion: The Ascending Injection Scale can be used to test back pain severity in Tswana speaking South Africans. I recommend that this scale be translated into the other black languages spoken in South Africa for testing and possible use.
A THESIS submitted in fulfillment for the degree of DOCTOR OF PHILOSOPHY. June 2015